Climate, history, and the modern world - Lamb, H. H. (London : New York : Routledge, 1995)
With the inclusion of new material, preface and illustrations, this 2nd edition of Lamb's acclaimed book covers issues of past and present climates, impacts on human affairs and an understanding of the problems of forecasting
Includes bibliographical references and index.
Keywords: Climatology